The European Union ombudsman in the public interest protection - a case study of the purchase of vaccines by the European Commission during the Covid-19 pandemic - Simic, Savo (Sociološki pregled, 2022)
In this paper, we examine the collision of private and public interests within the European Union in a case study of the mediation of the European Union Ombudsman in resolving a dispute between the European Commission and one civil society organization. The social justification and contribution of the research are reflected in the public interest in purchasing and procuring vaccines for the European public, while the scientific justification and contribution are present in deepening knowledge about the institutional and legal shortcomings on which the public interest of the European Union rests. The methods in use are: the analysis of the content of legal acts and other documentation of the European Union, the historical method in processing the institutional-historical role of the European Ombudsman institution and the new institutionalism present in the dynamic nature of institutions.
Keywords: Ombudsman; democracy; transparency; European Union; COVID-19